Translanguaging as a teaching resource in early language learning of English as a an additional language (EAL) - Laura Portolés (Universitat Autònoma de Barcelona, 2017)
Traditionally, language teaching has been grounded on a monolingual bias and the strict separation of languages has been conceived as a requirement to ensure foreign language learning success. However, the flexible use of one’s linguistic repertoire, known as translanguaging, has also proven beneficial in EFL settings (vid. Jones & Lewis, 2014). The present study aims at examining translanguaging practices in early language learning taking into account the functions proposed by García et al. (2011). Qualitative data were collected in 3 sessions of English for 25 Valencian kindergarteners. Participants (aged 4-5) were in their second year at a Catalan-immersion school, where other two languages are taught as media of instruction (Spanish and English). Results depict how very young language learners use their L1, L2 and L3 strategically in order to serve different communicative functions, without compromising their exposure to the target language (i.e. English). As a conclusion, we argue that a monolingual approach to teaching English as an additional language (EAL) is not a realistic picture of learners’ linguistic behaviour both inside and outside the classroom in multilingual settings.